The Effectiveness of Reproductive Hormone Use in the Farm: Application and Impact on the Fertility of Small Ruminants - Mustofa, Fatmawati; Prahara, Pupus Galau (Bulletin of Applied Animal Research, 2025)
Reproductive efficiency is one of the key factors in improving the productivity of small ruminants in meeting animal protein needs. Challenges such as oestrus detection, excessive calving intervals, suboptimal fertility, and high rates of pregnancy failure are still commonly encountered in traditional livestock farms. These obstacles are usually triggered by limitations in management in detecting oestrus and fulfilling nutritional needs, and can be overcome through the application of hormone utilisation technology in an effort to increase fertility. This review aims to evaluate the effectiveness of using reproductive hormones in the field and their impact on the fertility of small ruminants. Data from several literature sources were collected, including international and reputable national journals related to the use of prostaglandin, progesterone, and PMSG/eCG in oestrus synchronisation. The results show that the application of an effective hormonal protocols such as PGF2α administration, CIDR or progesterone sponge implantation with eCG, and the combination of PMSG use can increase oestrus response up to 100% and pregnancy rates above 90% under certain conditions. These variations are influenced by several factors, including livestock breed, management, and environment. The use of reproductive hormone technology is effective in improving reproductive efficiency in small ruminants, provided it is supported by proper husbandry management, adequate nutrition, and technical training. Therefore, it is recommended to develop local protocols based on available resources and conduct further research to optimise appropriate doses and hormone combinations under specific regional conditions. Keywords: reproductive hormones, fertility, small ruminants, oestrus synchronisation.